ChemInform Abstract: Facile Aromatization of 3, 4‐Dihydropyrimidin‐2(1H)‐ones (DHPMs) by Iodine. Issue 18 (11th April 2013) - Kodape, Manisha M.; Aswar, Anand S.; Gawhale, Nandkishor D.; Humne, Vivek T.; Mir, Bilal Ahmad
Abstract Microwave‐assisted, iodine‐mediated dehydrogenation of the substrates proceeds under mild conditions.